ANALISA PEREDAM INFLASI DI MUARA DATA MELALUI MAPING AREA PADA JUMLAH UANG BEREDAR - Etika Sabariah (Politeknik Bisnis Indonesia, 2022)
Abstract Inflation is part rutinitas jobs government. Inflation create high cost economic. To problem solving infect inflation is subsidi to not capable the people. But the way this is sometime arise new DWL factor. Goals riset is create development knowledgement teori audit social have character preventif not evaluation that focus to the amount money distributed. Place riset from informatin at internet about regulation government. Data collected passing observation information accident, and literatur review. Limits riset to facor inflation only relevancy timing and famine. Tools that use is basicly teority that testing implementation on the case in the room deduktif. Instrument riset is PBB, kinds jobs, BPJS healty, inflation regional, and probability behavior produsen and consumen that material to create maping area as operational variable the testing validitas and reabilitas passing logika reasoning that implementation tekhnik audit social from tracking the amount money distributed to maping area that, passing is create scenario audit social to pocket data, analytical audit social with maping area relevancy: 1) identification fluktiatif inventory and price, 2) flow subsidi, 3) correlation BPJS healty with administration asset, as well as recapitulation analytical audit social to estuary pocket data and analytical audit social to inefisiensi market accident because the poor resources Key Words: Inflation, Maping Area, Audit Socila, the amount money distributed, Preventif